The ubiquitin signal and autophagy: an orchestrated dance leading to mitochondrial degradation - Yamano, Koji (EMBO Rep, 2016)
The quality of mitochondria, essential organelles that produce ATP and regulate numerous metabolic pathways, must be strictly monitored to maintain cell homeostasis. The loss of mitochondrial quality control systems is acknowledged as a determinant for many types of neurodegenerative diseases including Parkinson's disease (PD). The two gene products mutated in the autosomal recessive forms of familial early‐onset PD, Parkin and PINK1, have been identified as essential proteins in the clearance of damaged mitochondria via an autophagic pathway termed mitophagy. Recently, significant progress has been made in understanding how the mitochondrial serine/threonine kinase PINK1 and the E3 ligase Parkin work together through a novel stepwise cascade to identify and eliminate damaged mitochondria, a process that relies on the orchestrated crosstalk between ubiquitin/phosphorylation signaling and autophagy. In this review, we highlight our current understanding of the detailed molecular mechanisms governing Parkin‐/PINK1‐mediated mitophagy and the evidences connecting Parkin/PINK1 function and mitochondrial clearance in neurons.